Adenofibroma in a Young Patient: A Rare Entity in an Uncommon Age - R. Maciel; S. Carvalho; M. Teixeira; M. J. Areias (Case Reports in Obstetrics and Gynecology)
Adenofibroma is an extremely uncommon benign tumor composed of glandular and fibrous tissues. It occurs more often in the endometrium but it can also occur in the cervix and extrauterine sites. We report a case of a 32-year-old asymptomatic woman with cervical adenofibroma, first detected in a routine endovaginal ultrasound, as a cervical mass containing multiple cystic components. Histopathologic findings diagnosed its nature. As adenofibromas are very rare, we present this case with a brief review of the literature.